Composite metal oxide supported palladium catalyst as well as preparation method and application thereof
By preparing a composite metal oxide-supported palladium catalyst, the problems of high dosage and low reaction efficiency in the prior art are solved, and the efficient and stable hydrogen debenzyl reaction in the preparation of CL-20 is achieved, reducing production costs.
Patent Information
- Application Number
- CN202411996312.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
AI Technical Summary
Prior Art In the preparation process of CL-20, the amount of palladium catalyst is used and the reaction efficiency is low, resulting in high production costs, and the catalyst is rapidly deactivated in the hydrodebenzyl reaction step, and the circulation performance is poor.
A composite metal oxide-supported palladium catalyst was prepared, and titanium dioxide gel was prepared by sol-gel method, and metal precursor was loaded by impregnation method to form a composite metal oxide support. Then Pd(OH)2 was loaded by deposition and precipitation method, and the loading of Pd was controlled to be between 5-10%.
The catalyst exhibits high reactivity, high selectivity and stability to the product in the hydrogen debenzyl reaction of HBIW, and rarely produces by-products, which significantly increases the yield of TAIW, reduces the amount of Pd, and reduces the production cost.
Smart Images

Figure BDA0005224582050000111 
Figure HDA0005224582060000011 
Figure HDA0005224582060000021
Abstract
Description
Technical Field
[0001] The invention relates to a composite metal oxide supported palladium catalyst and a preparation method thereof and application thereof in a hydrogenolysis benzylation reaction, belonging to the technical field of catalyst preparation. Background Art
[0002] Hexanitrohexaazaisowurtzitane is an important high-energy material compound, also known as HNIW or CL-20. It has the characteristics of high energy density, good oxygen balance, and good detonation performance. It is the best single energetic compound that can be industrially produced in the world today and has been widely studied in the fields of propellants and mixed explosives.
[0003] Nielsen et al. first introduced the method for synthesizing HNIW. The first step is the condensation of glyoxal and benzylamine to form hexabenzylhexaazaisowurtzitane (HBIW). The second step is the partial hydrogenolysis of HBIW to form tetraacetyldibenzylhexaazaisowurtzitane (TADBIW). The third step is the hydrogenolysis of TADBIW to form tetraacetylhexaazaisowurtzitane (TAIW). The last step is the nitration of TAIW to form CL-20. Among them, the hydrogenolysis of hexabenzylhexaazaisowurtzitane (HBIW) on a supported palladium catalyst is the most important step. At present, the preparation cost of CL-20 is high, and the two-step hydrogenation and debenzylation reaction only occurs in the presence of a palladium-based catalyst. In addition, the solvent system of the hydrogenolysis process is complex, and the palladium catalyst is rapidly deactivated in the first step of the hydrogenation and debenzylation reaction, and the cycle performance is poor. Although the catalysts reported so far have certain advantages, it is difficult to achieve high efficiency in catalyzing the hydrogenolysis and debenzylation of HBIW and TADBIW while reducing the amount of Pd to obtain high yield products. Therefore, selecting a suitable carrier to prepare Pd catalyst for more stable hydrogenolysis is one of the important ways to reduce the cost of CL-20.
[0004] The present invention prepares a composite metal oxide supported palladium catalyst, which has high reaction activity, high selectivity and stability for products, and produces very few by-products during the reaction process, thereby greatly improving the yield of TAIW. Summary of the invention
[0005] In order to solve the above problems, the present invention discloses a composite metal oxide supported palladium catalyst and a preparation method thereof and an application thereof in synthesizing TAIW through two-step hydrogenolysis debenzylation of HBIW.
[0006] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a composite metal oxide supported palladium catalyst, the composite metal oxide supported palladium catalyst comprising a composite metal oxide carrier and an active component Pd(OH)2 supported on the carrier, wherein the loading amount of the active component = mPd / (m Pd +m 载体 )×100%=5-10%, where m Pd It refers to the mass of palladium contained in the palladium precursor added during the preparation of the composite metal oxide-supported palladium catalyst;
[0008] The composite metal oxide carrier is prepared by the following method: using titanate as a titanium source, obtaining titanium dioxide gel by a sol-gel method, and obtaining a titanium precursor (which is amorphous titanium dioxide) after drying and grinding; loading a metal M precursor onto the titanium precursor by an impregnation method, and then drying and calcining to obtain a composite metal oxide carrier; the metal M precursor is selected from at least one of Zr(NO3)4·5H2O, SnCl2, Ce(NO3)3·6H2O, La(NO3)3·6H2O and Mn(NO3)2·4H2O; the titanium precursor and the metal M precursor are mixed according to the metal M loading amount x%=m 金属M氧化物 / m TiO2 ×100% = 1-9% feed, where m 金属M氧化物 It is the total mass of metal M oxide converted from the mass of metal M element contained in the metal M precursor, m TiO2 Refers to the mass of the titanium precursor.
[0009] Preferably, the titanate is at least one of tetraethyl titanate, tetraisopropyl titanate and tetrabutyl titanate.
[0010] Preferably, the sol-gel method for obtaining titanium dioxide gel is implemented as follows: dissolving titanate in anhydrous ethanol to obtain solution A; adding water or an aqueous solution of an inorganic compound dropwise to solution A under stirring to obtain solution B, after a period of time, solution B turns white, stirring is continued for 20-30 hours (more preferably 24 hours) and then centrifuged to obtain a white solid, which is titanium dioxide gel; the inorganic compound is ammonia water or phosphoric acid.
[0011] Preferably, the drying condition of the titanium dioxide gel is: drying at 90-120° C. for 2-4 hours in a forced air drying oven.
[0012] Preferably, the impregnation method is an equal volume impregnation method.
[0013] Preferably, after the metal M precursor is loaded onto the titanium precursor by the impregnation method, the drying is first air-dried at room temperature and then dried in a forced air drying oven at 90-120° C. for 2-4 hours.
[0014] Preferably, the calcination conditions are: heating to 450-500° C. at 5-10° C. / min in a muffle furnace and calcining for 6-8 hours.
[0015] Preferably, x is 3-9, more preferably 3-5.
[0016] Preferably, the loading amount of the active component is 10 wt%.
[0017] In a second aspect, the present invention provides a method for preparing the composite metal oxide-supported palladium catalyst according to the first aspect, comprising the following steps:
[0018] (1) obtaining a composite metal oxide support;
[0019] (2) The composite metal oxide supported palladium catalyst was prepared by the deposition precipitation method.
[0020] Preferably, step (2) is specifically implemented as follows: disperse the composite metal oxide carrier in deionized water, stir and heat to 50-80°C in a water bath, add the palladium precursor solution and stir at 50-80°C for 4-6h, then adjust the solution pH to 9-11, continue to stir at this temperature for 1-2h, finally stir at room temperature for 1-2h, filter with suction, dry, and finally grind into powder uniformly to obtain a composite metal oxide-supported palladium catalyst.
[0021] As a further preference, in step (2), the palladium precursor is at least one of palladium chlorate, palladium nitrate, and dichlorotetraamminepalladium.
[0022] As a further preference, in step (2), an aqueous solution of an alkaline substance is added to adjust the solution pH to 9-11, and the alkaline substance is at least one of sodium hydroxide, potassium hydroxide, and ammonia water.
[0023] As a further preference, in step (2), the drying is performed in a vacuum drying oven at 90-120° C. for 20-30 h.
[0024] In the third aspect, the present invention provides the use of the composite metal oxide supported palladium catalyst in the synthesis of TAIW via a two-step hydrogenolysis debenzylation reaction of HBIW.
[0025] Preferably, the synthesis of TAIW by two-step hydrogenolysis of HBIW is carried out according to the following steps:
[0026] Step 1 (first step hydrogenolysis benzylation reaction): HBIW, DMF, PhBr, composite metal oxide-supported palladium catalyst, and Ac2O are sequentially added to a reaction kettle, the air in the reaction kettle is replaced with hydrogen, hydrogen is introduced, and the reaction is carried out for 18-36 hours under the reaction conditions of 0.5-1MPa, 25-40°C, and a constant speed of 500-1000r / min, the reaction is stopped, and an off-white solid is obtained by filtering and washing. The off-white solid is TADBIW and the catalyst, and the solid is placed in a blast drying oven at 90-120°C and dried for 2-4 hours;
[0027] Step 2 (second step hydrogenolysis benzyl reaction): Pour the solid obtained in step 1 into a reactor and add an appropriate amount of acetic acid, set the temperature to 60-70°C and stir for 1-4h, then stop stirring, add a certain amount of composite metal oxide-loaded palladium catalyst and an appropriate amount of deionized water, then pass H2 to replace the air in the reactor, and then continue to pass H2 to make the pressure in the reactor at 1.5-3MPa, set the reaction temperature to 60-70°C and start the reaction, keep the speed constant at 500-1000r / min, stop the reaction after 12-24h, filter and wash, the obtained black solid is the catalyst, and the obtained filtrate is the solution containing TAIW, which is treated and tested for the purity of the product by HPLC to obtain the TAIW yield.
[0028] Preferably, the feed ratio of HBIW, DMF, PhBr, composite metal oxide-supported palladium catalyst, and Ac2O is 15 g: 127 ml: 0.3 ml: 0.2 g: 21 ml.
[0029] Preferably, the feed mass ratio of the HBIW to the composite metal oxide-supported palladium catalyst added again is 15:0.2.
[0030] Compared with the prior art, the present invention has the following advantages:
[0031] 1) The composite metal oxide supported palladium catalyst prepared in the present invention generates oxygen vacancies (O V ), so the surface of the composite metal oxide support is enriched with O V , O is formed on the surface V It may induce additional metal-support interactions and hinder metal agglomeration during catalyst preparation.
[0032] 2) The composite metal oxide-supported palladium catalyst prepared in the present invention makes it easier for the electron-rich Pd species to activate the adsorbed hydrogenation reaction, thereby promoting the catalytic hydrogenation activity.
[0033] 3) The composite metal oxide-supported palladium catalyst prepared in the present invention makes the Pd species on the catalyst more dispersed, increases the effective active sites, and is more conducive to the contact and reaction between the reactants and the active centers.
[0034] 4) The composite metal oxide-supported palladium catalyst of the present invention is used in the hydrogenolysis debenzylation reaction of HBIW and TADBIW to obtain a high yield product, and the amount of Pd used is reduced, which can reduce the production cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 is the XRD pattern of the 10% Pd-5% TiCe catalyst prepared in Example 2;
[0036] Figure 2 is a TEM image of the 10% Pd-5% TiCe catalyst prepared in Example 2;
[0037] Figure 3 This is the elemental analysis diagram of the 10% Pd-5% TiCe catalyst prepared in Example 2. DETAILED DESCRIPTION
[0038] The technical solution of the present invention is described in more detail below in conjunction with the embodiments. The protection scope of the present invention is not limited to the following specific implementation methods.
[0039] Example 1
[0040] (1) Preparation of TiO2
[0041] Pour 150ml of anhydrous ethanol into a beaker and place it on a magnetic stirrer to stir. Then, pour 6.7ml of tetraethyl titanate into the anhydrous ethanol to prepare solution A. After stirring evenly, add 2.7ml of 22-28wt% ammonia water dropwise into solution A to prepare solution B. After a period of time, solution B turns white. Continue stirring for 24 hours and then centrifuge to obtain a white solid. Dry it in a blast drying oven at 90°C for 2 hours, take it out, grind it, and obtain a titanium precursor.
[0042] (2) Preparation of composite metal oxide support MTi (M is another metal)
[0043] The carrier CeTi was prepared by an equal volume impregnation method: 2.00 g of the titanium precursor obtained in step (1) was weighed, 0.2523 g of Ce(NO3)3·6H2O was dissolved in an appropriate amount of water, and then poured into a culture dish containing the titanium precursor, and stirred continuously with a glass rod until the color was uniform, and then air-dried at room temperature. After air-drying, it was dried at 90°C in a forced air drying oven for 2 h, taken out and poured into a crucible, and heated to 450°C in a muffle furnace at 5°C / min, and calcined for 6 h to obtain Ce-TiO2 powder, which was recorded as CeTi-5;
[0044] (3) Preparation of Pd(OH)2 / MTi-x catalyst
[0045] Prepare Pd(OH)2 / MTi-x catalyst (10wt.%Pd) by deposition precipitation method: take 1.8g of the carrier obtained in step (2) into a beaker, pour in 70ml of deionized water, stir and heat to 50℃ in a water bath, add 4.00mL of H2PdCl4 solution with a Pd concentration of 0.05g / mL and keep stirring at 50℃ for 4h, then add 1M potassium hydroxide aqueous solution to adjust the solution pH to 9, continue to keep stirring for 1h, finally stir at room temperature for 1h, filter, dry the catalyst in a vacuum oven at 90℃ for 24h, and finally grind into powder evenly to obtain 10wt.%Pd(OH)2 / CeTi-5 catalyst.
[0046] Example 2
[0047] (1) Preparation of TiO2
[0048] Pour 150ml of anhydrous ethanol into a beaker and place it on a magnetic stirrer for stirring. Then, pour 10ml of tetrabutyl titanate into the anhydrous ethanol to obtain solution A. After stirring evenly, add 4ml of 22-28wt% ammonia water dropwise into solution A to obtain solution B. After a period of time, solution B turns white. Continue stirring for 24 hours and centrifuge to obtain a white solid. Dry it in a forced air drying oven at 110°C for 2 hours, take it out, grind it, and obtain a titanium precursor.
[0049] (2) Preparation of composite metal oxide support MTi (M is another metal)
[0050] The carrier CeTi was prepared by an equal volume impregnation method: 2.00 g of the titanium precursor obtained in step (1) was weighed, 0.2523 g of Ce(NO3)3·6H2O was dissolved in an appropriate amount of water, and then poured into a culture dish containing the titanium precursor, and stirred continuously with a glass rod until the color was uniform, and then air-dried at room temperature. After air-drying, it was dried at 110°C in a forced air drying oven for 2 h, taken out and poured into a crucible, and heated to 450°C in a muffle furnace at 5°C / min, and calcined for 6 h to obtain Ce-TiO2 powder, which was recorded as CeTi-5;
[0051] (3) Preparation of Pd(OH)2 / MTi-x catalyst
[0052] Prepare Pd(OH)2 / MTi-x catalyst (10wt.%Pd) by deposition precipitation method: take 1.8g of the carrier obtained in step (2) into a beaker, pour in 70ml of deionized water, stir and heat to 70℃ in a water bath, add 4.00mL of H2PdCl4 solution with a Pd concentration of 0.05g / mL and keep stirring at 70℃ for 5h, then add 1M sodium hydroxide solution to adjust the solution pH to 10, continue to keep stirring for 1h, finally stir at room temperature for 1h, filter, dry the catalyst in a vacuum oven at 110℃ for 24h, and finally grind into powder evenly to obtain 10wt.%Pd(OH)2 / CeTi-5 catalyst.
[0053] Example 3
[0054] (1) Preparation of TiO2
[0055] Pour 150ml of anhydrous ethanol into a beaker and place it on a magnetic stirrer to stir. Then, pour 10ml of tetrabutyl titanate into the anhydrous ethanol to obtain solution A. After stirring evenly, add 4ml of 22-28wt% ammonia water dropwise into solution A to obtain solution B. After a period of time, solution B turns white. Continue stirring for 24 hours and centrifuge to obtain a white solid. Dry it in a forced air drying oven at 100°C for 3 hours, take it out, grind it, and obtain a titanium precursor.
[0056] (2) Preparation of composite metal oxide support MTi (M is another metal)
[0057] The carrier CeTi was prepared by an equal volume impregnation method: 2.00 g of the titanium precursor obtained in step (1) was weighed, 0.1514 g of Ce(NO3)3·6H2O was dissolved in an appropriate amount of water, and then poured into a culture dish containing the titanium precursor, and stirred continuously with a glass rod until the color was uniform, and then air-dried at room temperature. After air-drying, it was dried at 100°C in a forced air drying oven for 3 h, taken out and poured into a crucible, and heated to 500°C at 5°C / min in a muffle furnace, and calcined for 6 h to obtain Ce-TiO2 powder, which was recorded as CeTi-3;
[0058] (3) Preparation of Pd(OH)2 / MTi-x catalyst
[0059] Prepare Pd(OH)2 / MTi-x catalyst (10wt.%Pd) by deposition precipitation method: take 1.8g of the carrier obtained in step (2) into a beaker, pour in 70ml of deionized water, stir and heat to 70℃ in a water bath, add 4.00mL of H2PdCl4 solution with a Pd concentration of 0.05g / mL and keep stirring at 70℃ for 5h, then add 1M ammonia solution to adjust the pH of the solution to 10, continue to keep stirring for 1h, finally stir at room temperature for 1h, filter, dry the catalyst in a vacuum oven at 100℃ for 24h, and finally grind into powder evenly to obtain 10wt.%Pd(OH)2 / CeTi-3 catalyst.
[0060] Example 4
[0061] (1) Preparation of TiO2
[0062] Pour 150ml of anhydrous ethanol into a beaker and place it on a magnetic stirrer to stir. Then, pour 10ml of tetrabutyl titanate into the anhydrous ethanol to obtain solution A. After stirring evenly, add 3ml of water dropwise into solution A to obtain solution B. After a period of time, solution B turns white. Continue stirring for 24 hours and then centrifuge to obtain a white solid. Dry it in a forced air drying oven at 90°C for 4 hours, take it out, grind it, and obtain a titanium precursor.
[0063] (2) Preparation of composite metal oxide support MTi (M is another metal)
[0064] The carrier CeTi was prepared by an equal volume impregnation method: 2.00 g of the titanium precursor obtained in step (1) was weighed, 0.1514 g of Ce(NO3)3·6H2O was dissolved in an appropriate amount of water, and then poured into a culture dish containing the titanium precursor, and stirred continuously with a glass rod until the color was uniform, and then air-dried at room temperature. After air-drying, it was dried at 90°C in a forced air drying oven for 4 h, taken out and poured into a crucible, and heated to 440°C in a muffle furnace at 5°C / min, and calcined for 6 h to obtain Ce-TiO2 powder, which was recorded as CeTi-3;
[0065] (3) Preparation of Pd(OH)2 / MTi-x catalyst
[0066] Prepare Pd(OH)2 / MTi-x catalyst (10wt.%Pd) by deposition precipitation method: take 1.8g of the carrier obtained in step (2) into a beaker, pour in 70ml of deionized water, stir and heat to 70℃ in a water bath, add 4.00mL of H2PdCl4 solution with a Pd concentration of 0.05g / mL and keep stirring at 70℃ for 5h, then add 1M sodium hydroxide solution to adjust the pH of the solution to 10, continue to keep stirring for 1h, finally stir at room temperature for 1h, filter, dry the catalyst in a vacuum oven at 90℃ for 24h, and finally grind into powder evenly to obtain 10wt.%Pd(OH)2 / CeTi-3 catalyst.
[0067] Example 5
[0068] (1) Preparation of TiO2
[0069] Pour 150ml of anhydrous ethanol into a beaker and place it on a magnetic stirrer to stir. Then, pour 6.7ml of tetraethyl titanate into the anhydrous ethanol to obtain solution A. After stirring evenly, add 2ml of water dropwise into solution A to obtain solution B. After a period of time, solution B turns white. Continue stirring for 24 hours and centrifuge to obtain a white solid. Dry it in a forced air drying oven at 100°C for 2 hours, take it out, grind it, and obtain a titanium precursor.
[0070] (2) Preparation of composite metal oxide support MTi (M is another metal)
[0071] The carrier CeTi was prepared by an equal volume impregnation method: 2.00 g of the titanium precursor obtained in step (1) was weighed, 0.353 g of Ce(NO3)3·6H2O was dissolved in an appropriate amount of water, and then poured into a culture dish containing the titanium precursor, and stirred continuously with a glass rod until the color was uniform, and then air-dried at room temperature. After air-drying, it was dried at 100°C in a forced air drying oven for 2 h, taken out and poured into a crucible, and heated to 500°C at 10°C / min in a muffle furnace, and calcined for 8 h to obtain Ce-TiO2 powder, which was recorded as CeTi-7;
[0072] (3) Preparation of Pd(OH)2 / MTi-x catalyst
[0073] Prepare Pd(OH)2 / MTi-x catalyst (10wt.%Pd) by deposition precipitation method: take 1.8g of the carrier obtained in step (2) into a beaker, pour in 70ml of deionized water, stir and heat to 70℃ in a water bath, add 10.00mL of palladium nitrate aqueous solution with a Pd concentration of 0.02g / mL, keep stirring at 70℃ for 5h, then add 1M sodium hydroxide solution to adjust the solution pH to 10, continue to keep stirring for 1h, finally stir at room temperature for 1h, filter, dry the catalyst in a vacuum oven at 90℃ for 24h, and finally grind into powder evenly to obtain 10wt.%Pd(OH)2 / CeTi-7 catalyst.
[0074] Example 6
[0075] (1) Preparation of TiO2
[0076] Pour 150ml of anhydrous ethanol into a beaker and place it on a magnetic stirrer to stir. Then, pour 6.7ml of tetraethyl titanate into the anhydrous ethanol to obtain solution A. After stirring evenly, add 2.7ml of 22-28wt% ammonia water dropwise into solution A to obtain solution B. After a period of time, solution B turns white. Continue stirring for 24 hours and then centrifuge to obtain a white solid. Dry it in a forced air drying oven at 110°C for 3 hours, take it out, grind it, and obtain a titanium precursor.
[0077] (2) Preparation of composite metal oxide support MTi (M is another metal)
[0078] The carrier CeTi was prepared by an equal volume impregnation method: 2.00 g of the titanium precursor obtained in step (1) was weighed, 0.353 g of Ce(NO3)3·6H2O was dissolved in an appropriate amount of water, and then poured into a culture dish containing the titanium precursor, and stirred continuously with a glass rod until the color was uniform, and then air-dried at room temperature. After air-drying, it was dried at 110°C in a forced air drying oven for 3 h, taken out and poured into a crucible, and heated to 450°C in a muffle furnace at 10°C / min, and calcined for 6 h to obtain Ce-TiO2 powder, which was recorded as CeTi-7;
[0079] (3) Preparation of Pd(OH)2 / MTi-x catalyst
[0080] Prepare Pd(OH)2 / MTi-x catalyst (10wt.%Pd) by deposition precipitation method: take 1.8g of the carrier obtained in step (2) into a beaker, pour in 70ml of deionized water, stir and heat to 70℃ in a water bath, add 10.00mL of palladium nitrate aqueous solution with a Pd concentration of 0.02g / mL, keep stirring at 70℃ for 5h, then add 1M potassium hydroxide solution to adjust the solution pH to 10, continue to keep stirring for 1h, finally stir at room temperature for 1h, filter, dry the catalyst in a vacuum oven at 110℃ for 24h, and finally grind into powder evenly to obtain 10wt.%Pd(OH)2 / CeTi-7 catalyst.
[0081] Example 7
[0082] (1) Preparation of TiO2
[0083] Pour 150ml of anhydrous ethanol into a beaker and place it on a magnetic stirrer to stir. Then, pour 10ml of tetraisopropyl titanate into the anhydrous ethanol to prepare solution A. After stirring evenly, add 4ml of 22-28wt% ammonia water dropwise into solution A to prepare solution B. After a period of time, solution B turns white. Continue stirring for 24 hours and then centrifuge to obtain a white solid. Dry it in a forced air drying oven at 110°C for 2 hours, take it out, grind it, and obtain a titanium precursor.
[0084] (2) Preparation of composite metal oxide support MTi (M is another metal)
[0085] The carrier CeTi was prepared by an equal volume impregnation method: 2.00 g of the titanium precursor obtained in step (1) was weighed, 0.454 g of Ce(NO3)3·6H2O was dissolved in an appropriate amount of water, and then poured into a culture dish containing the titanium precursor, and stirred continuously with a glass rod until the color was uniform, and then air-dried at room temperature. After air-drying, it was dried at 110°C in a forced air drying oven for 2 h, taken out and poured into a crucible, and heated to 460°C in a muffle furnace at 10°C / min, and calcined for 6 h to obtain Ce-TiO2 powder, which was recorded as CeTi-9;
[0086] (3) Preparation of Pd(OH)2 / MTi-x catalyst
[0087] Prepare Pd(OH)2 / MTi-x catalyst (10wt.%Pd) by deposition precipitation method: take 1.8g of the carrier obtained in step (2) into a beaker, pour in 70ml of deionized water, stir and heat to 80℃ in a water bath, add 10.00mL of dichlorotetraamminepalladium solution with a Pd concentration of 0.02g / mL, keep stirring at 80℃ for 5h, then add 1M ammonia solution to adjust the pH of the solution to 10, continue to keep stirring for 1h, finally stir at room temperature for 1h, filter, dry the catalyst in a vacuum oven at 110℃ for 24h, and finally grind into powder evenly to obtain 10wt.%Pd(OH)2 / CeTi-9 catalyst.
[0088] Example 8
[0089] (1) Preparation of TiO2
[0090] Pour 150ml of anhydrous ethanol into a beaker and place it on a magnetic stirrer to stir. Then, pour 10ml of tetraisopropyl titanate into the anhydrous ethanol to obtain solution A. After stirring evenly, add 3ml of water dropwise into solution A to obtain solution B. After a period of time, solution B turns white. Continue stirring for 24 hours and then centrifuge to obtain a white solid. Dry it in a forced air drying oven at 90°C for 2 hours, take it out, grind it, and obtain a titanium precursor.
[0091] (2) Preparation of composite metal oxide support MTi (M is another metal)
[0092] The carrier CeTi was prepared by an equal volume impregnation method: 2.00 g of the titanium precursor obtained in step (1) was weighed, 0.454 g of Ce(NO3)3·6H2O was dissolved in an appropriate amount of water, and then poured into a culture dish containing the titanium precursor, and stirred continuously with a glass rod until the color was uniform, and then air-dried at room temperature. After air-drying, it was dried at 90°C in a forced air drying oven for 2 h, taken out and poured into a crucible, and heated to 480°C in a muffle furnace at 10°C / min, and calcined for 6 h to obtain Ce-TiO2 powder, which was recorded as CeTi-9;
[0093] (3) Preparation of Pd(OH)2 / MTi-x catalyst
[0094] Prepare Pd(OH)2 / MTi-x catalyst (10wt.%Pd) by deposition precipitation method: take 1.8g of the carrier obtained in step (2) into a beaker, pour in 70ml of deionized water, stir and heat to 50℃ in a water bath, add 10.00mL of palladium nitrate aqueous solution with a Pd concentration of 0.02g / mL, keep stirring at 50℃ for 5h, then add 1M ammonia solution to adjust the pH of the solution to 10, continue to keep stirring for 1h, finally stir at room temperature for 1h, filter, dry the catalyst in a vacuum oven at 90℃ for 24h, and finally grind into powder evenly to obtain 10wt.%Pd(OH)2 / CeTi-9 catalyst.
[0095] Example 9
[0096] (1) Preparation of TiO2
[0097] Pour 150ml of anhydrous ethanol into a beaker and place it on a magnetic stirrer to stir. Then, pour 10ml of tetrabutyl titanate into the anhydrous ethanol to prepare solution A. After stirring evenly, add 4ml of 22-28wt% ammonia water dropwise into solution A to prepare solution B. After a period of time, solution B turns white. Continue stirring for 24 hours and then centrifuge to obtain a white solid. Dry it in a forced air drying oven at 110°C for 2 hours, take it out, grind it, and obtain a titanium precursor.
[0098] (2) Preparation of composite metal oxide support MTi (M is another metal)
[0099] The carrier ZrTi was prepared by an equal volume impregnation method: 2.00 g of the titanium precursor obtained in step (1) was weighed, 0.2236 g of Zr(NO3)4·5H2O was dissolved in an appropriate amount of water, and then poured into a culture dish containing the titanium precursor, and stirred continuously with a glass rod until the color was uniform, and then air-dried at room temperature. After air-drying, it was dried in a forced air drying oven at 110°C for 2 h, taken out and poured into a crucible, and heated to 450°C in a muffle furnace at 5°C / min, and calcined for 6 h to obtain Zr-TiO2 powder, recorded as ZrTi-3;
[0100] (3) Preparation of Pd(OH)2 / MTi-x catalyst
[0101] Prepare Pd(OH)2 / MTi-x catalyst (10wt.%Pd) by deposition precipitation method: take 1.8g of the carrier obtained in step (2) into a beaker, pour in 70ml of deionized water, stir and heat to 70℃ in a water bath, add 4.00mL of H2PdCl4 solution with a Pd concentration of 0.05g / mL and keep stirring at 70℃ for 5h, then add 1M sodium hydroxide solution to adjust the solution pH to 10, continue to keep stirring for 1h, finally stir at room temperature for 1h, filter, dry the catalyst in a vacuum oven at 110℃ for 24h, and finally grind into powder evenly to obtain 10wt.%Pd(OH)2 / ZrTi-3 catalyst.
[0102] Example 10
[0103] (1) Preparation of TiO2
[0104] Pour 150ml of anhydrous ethanol into a beaker and place it on a magnetic stirrer to stir. Then, pour 10ml of tetrabutyl titanate into the anhydrous ethanol to prepare solution A. After stirring evenly, add 4ml of 22-28wt% ammonia water dropwise into solution A to prepare solution B. After a period of time, solution B turns white. Continue stirring for 24 hours and then centrifuge to obtain a white solid. Dry it in a forced air drying oven at 110°C for 2 hours, take it out, grind it, and obtain a titanium precursor.
[0105] (2) Preparation of composite metal oxide support MTi (M is another metal)
[0106] The carrier SnTi was prepared by an equal volume impregnation method: 2.00 g of the titanium precursor obtained in step (1) was weighed, 0.1037 g of SnCl2 was dissolved in an appropriate amount of water, and then poured into a culture dish containing the titanium precursor, and stirred continuously with a glass rod until the color was uniform, and then air-dried at room temperature. After air-drying, it was dried in a forced air drying oven at 110°C for 2 h, taken out and poured into a crucible, and heated to 450°C in a muffle furnace at 5°C / min, and calcined for 6 h to obtain Sn-TiO2 powder, which was recorded as SnTi-3;
[0107] (3) Preparation of Pd(OH)2 / MTi-x catalyst
[0108] Prepare Pd(OH)2 / MTi-x catalyst (10wt.%Pd) by deposition precipitation method: take 1.8g of the carrier obtained in step (2) into a beaker, pour in 70ml of deionized water, stir and heat to 70℃ in a water bath, add 4.00mL of H2PdCl4 solution with a Pd concentration of 0.05g / mL and keep stirring at 70℃ for 5h, then add 1M sodium hydroxide solution to adjust the solution pH to 10, continue to keep stirring for 1h, finally stir at room temperature for 1h, filter, dry the catalyst in a vacuum oven at 110℃ for 24h, and finally grind into powder evenly to obtain 10wt.%Pd(OH)2 / SnTi-3 catalyst.
[0109] Embodiment 11
[0110] The application of composite metal oxide-supported palladium catalysts in different proportions prepared in Examples 1 to 10 in hydrogenolysis-debenzylation reactions was investigated.
[0111] 15g HBIW, 127ml DMF, 0.3ml PhBr, 0.2g of the above-prepared composite metal oxide supported palladium catalyst, and 21ml Ac2O were added to a 250ml reactor in sequence, and the air in the reactor was replaced with hydrogen. Hydrogen was introduced, and the reaction was carried out for 24 hours under the reaction conditions of 0.5MPa, 25°C, and a constant speed of 1000r / min. The reaction was stopped, and the reaction solution was filtered using an organic filter membrane and washed with ethanol to obtain an off-white solid. The off-white solid is TADBIW and a catalyst. The solid was placed in a blast drying oven at 110°C and dried for 2h, then taken out and weighed. The dried solid was poured into a reactor and 127ml of acetic acid was added, and the temperature was set to 60°C and stirred for 2h. After 2 hours, stirring was stopped, 0.2 g of composite metal oxide-supported palladium catalyst and 18 ml of deionized water were added, and H2 was passed to replace the air in the kettle. Then H2 was continued to be passed to make the pressure in the kettle at 1.5 MPa. The reaction temperature was set to 60 ° C and the reaction was started. The speed was constant at 1000 r / min. The reaction was stopped after 24 hours of reaction. The reaction solution was filtered using an organic filter membrane and washed with acetic acid. The obtained black solid was the catalyst. The solid was placed in a blast drying oven at 110 ° C and dried for 2 hours, then taken out and weighed. After the TADBIW hydrogenolysis reaction was completed, HPLC was used to detect the purity of the product to obtain the TAIW yield. The experimental results are shown in Table 1.
[0112] Table 1 Hydrogenolysis performance of palladium catalysts supported on composite metal oxides at different ratios
[0113] catalyst TADBIW yield (%) TAIW yield (%) Example 1 77.26 99.00 Example 2 78.13 99.26 Example 3 75.66 83.40 Example 4 75.36 85.54 Example 5 75.34 96.44 Example 6 76.13 95.64 Example 7 75.00 96.54 Example 8 75.13 97.22 Example 9 77.86 84.33 Example 10 77.13 84.46
[0114] Examples 12 to 19
[0115] 15g HBIW, 127ml DMF, 0.3ml PhBr, 0.2g 10% Pd-CeTi-5% catalyst prepared in Example 2, and 21ml Ac2O were added to a 250ml reactor in sequence, and the air in the reactor was replaced with hydrogen. Hydrogen was introduced, and the temperature and hydrogen pressure were raised to the required range of the reactor. Stirring began, and the speed was constant at 1000r / min. The reaction was continued for 24 hours, and the reaction was stopped. The reaction solution was filtered using an organic filter membrane and washed with ethanol to obtain an off-white solid. The off-white solid was TADBIW and a catalyst. The solid was placed in a forced air drying oven at 110°C and dried for 2h before being taken out and weighed. The dried solid was poured into a reactor and 127ml of acetic acid was added, and the temperature was set to 60°C and stirred for 2h. After 2 hours, stirring was stopped, 0.2 g of 10% Pd-CeTi-5% catalyst prepared in Example 2 and 18 ml of deionized water were added, and H2 was passed to replace the air in the reactor, and then H2 was continued to be passed. After the temperature and hydrogen pressure were raised to the required range of the reactor, stirring was started, and the speed was constant at 1000 r / min. The reaction was stopped after 24 hours of reaction. The reaction solution was filtered using an organic filter membrane and washed with acetic acid, and the obtained black solid was the catalyst. The solid was placed in a forced air drying oven at 110°C and dried for 2 hours, then taken out and weighed. After the TADBIW hydrogenolysis reaction was completed, HPLC was used to detect the purity of the product to obtain the TAIW yield. The experimental results are shown in Table 2.
[0116] Table 2 Hydrogenolysis performance of composite metal oxide supported palladium catalysts under different hydrogenation reaction conditions
[0117]
[0118] Embodiment 20
[0119] Example 20 investigates the application performance of the composite metal oxide supported palladium catalyst prepared in Example 2 in the hydrogenolysis benzyl application. 15g HBIW, 127ml DMF, 0.3ml PhBr, 0.2g 10% Pd-CeTi-5% catalyst prepared in Example 2, and 21ml Ac2O were added to a 250ml reactor in sequence, the air in the reactor was replaced with hydrogen, hydrogen was introduced, the temperature was raised to 25°C, the hydrogen pressure was 0.5MPa, stirring was started, the speed was constant at 1000r / min, the reaction was performed for 24 hours, the reaction was stopped, the reaction solution was filtered using an organic filter membrane and washed with ethanol to obtain an off-white solid. The off-white solid is TADBIW and a catalyst. The solid was placed in a forced air drying oven at 110°C and dried for 2h before being taken out and weighed. The dried solid was poured into a reactor and 127ml of acetic acid was added, and the temperature was set to 60°C and stirred for 2h. After 2 hours, stirring was stopped, 0.2g of 10% Pd-CeTi-5% catalyst prepared in Example 2 and 18ml of deionized water were added, and H2 was passed to replace the air in the kettle, and then H2 was continued to be passed, the temperature was raised to 60°C, the hydrogen pressure was 1.5MPa, stirring was started, and the speed was constant at 1000r / min. The reaction was stopped after 24 hours of reaction. The reaction solution was filtered using an organic filter membrane and washed with acetic acid, and the obtained black solid was the catalyst. The solid was placed in a forced air drying oven at 110°C and dried for 2 hours, then taken out and weighed. After the TADBIW hydrogenolysis reaction was completed, HPLC was used to detect the purity of the product to obtain the TAIW yield. The catalyst after the reaction continued to be applied to the experiment, and 0.02g of fresh catalyst from Example 2 was added before each feeding. The experimental conditions were the same, and the experimental results are shown in Table 3.
[0120] Table 3 Application performance of composite metal oxide supported palladium catalyst
[0121] Number of applications TADBIW yield (%) TAIW yield (%) 1 78.13 99.26 2 74.47 94.69 3 74.93 97.98
[0122] Comparative Example 1 (Compared with Example 2)
[0123] Comparative Example 1: The reaction performance of CeO2-supported palladium catalyst was investigated.
[0124] (1) Preparation of Pd(OH)2 / CeO2 catalyst
[0125] Pd(OH)2 / MTi-x catalyst (10wt.% Pd) was prepared by deposition precipitation method: 1.8g CeO2 was taken into a beaker, 70ml deionized water was poured in, stirred and heated to 70℃ in a water bath, 4.00mL H2PdCl4 solution with a Pd concentration of 0.05g / mL was added, and the mixture was kept warm and stirred at 70℃ for 5h, then 1M sodium hydroxide solution was added to adjust the pH of the solution to 10, and the mixture was kept warm and stirred for 1h, and finally stirred at room temperature for 1h, filtered, and the catalyst was dried in a vacuum oven at 110℃ for 24h, and finally ground into powder to obtain 10wt.% Pd(OH)2 / CeO2 catalyst.
[0126] (2) 15 g HBIW, 127 ml DMF, 0.3 ml PhBr, 0.2 g of the prepared composite metal oxide supported palladium catalyst, and 21 ml Ac2O were added to a 250 ml reactor in sequence, the air in the reactor was replaced with hydrogen, hydrogen was introduced, and the reaction was carried out for 24 hours under the reaction conditions of 0.5 MPa, 25°C, and a constant speed of 1000 r / min. The reaction was stopped, and the reaction solution was filtered using an organic filter membrane and washed with ethanol to obtain an off-white solid. The off-white solid is TADBIW and the catalyst. The yield of TADBIW was 75.57%. The solid was placed in a forced air drying oven at 110°C and dried for 2 hours, then taken out and weighed. The dried solid was poured into a reactor and 127 ml of acetic acid was added, and the temperature was set to 60°C and stirred for 2 hours. After 2 hours, stirring was stopped, 0.2 g 10 wt.% Pd(OH)2 / CeO2 catalyst and 18 ml deionized water were added, and H2 was passed to replace the air in the kettle. Then H2 was continued to be passed to make the pressure in the kettle at 1.5 MPa. The reaction temperature was set to 60°C and the reaction was started. The speed was kept constant at 1000 r / min. The reaction was stopped after 24 hours of reaction. The reaction solution was filtered using an organic filter membrane and washed with acetic acid. The obtained black solid was the catalyst. The solid was placed in a forced air drying oven at 110°C and dried for 2 hours, then taken out and weighed. After the TADBIW hydrogenolysis reaction was completed, HPLC was used to detect the purity of the product, and a TAIW yield of 51.71% was obtained.
[0127] Comparative Example 2 (Compare with Example 2)
[0128] Comparative Example 2: The reaction performance of NiTi composite metal oxide supported palladium catalyst was investigated.
[0129] (1) Preparation of TiO2
[0130] Pour 150ml of anhydrous ethanol into a beaker and place it on a magnetic stirrer to stir. Then, pour 10ml of tetrabutyl titanate into the anhydrous ethanol to prepare solution A. After stirring evenly, add 4ml of 22-28wt% ammonia water dropwise into solution A to prepare solution B. After a period of time, solution B turns white. Continue stirring for 24 hours and then centrifuge to obtain a white solid. Dry it in a forced air drying oven at 110°C for 2 hours, take it out, grind it, and obtain a titanium precursor.
[0131] (2) Preparation of different composite metal oxide supports MTi (M is another metal)
[0132] The carrier NiTi was prepared by an equal volume impregnation method: 2.00 g of the titanium precursor obtained in step (1) was weighed, 0.3893 g of Ni(NO3)2·6H2O was dissolved in an appropriate amount of water, and then poured into a culture dish containing the titanium precursor, and stirred continuously with a glass rod until the color was uniform, and then air-dried at room temperature. After air-drying, it was dried at 110°C in a forced air drying oven for 2 h, taken out and poured into a crucible, and heated to 450°C in a muffle furnace at 5°C / min, and calcined for 6 h to obtain Ni-TiO2 powder, which was recorded as NiTi-5;
[0133] (3) Preparation of Pd(OH)2 / MTi-x catalyst
[0134] Prepare Pd(OH)2 / MTi-x catalyst (10wt.%Pd) by deposition precipitation method: take 1.8g of the carrier obtained in step (2) into a beaker, pour in 70ml of deionized water, stir and heat to 70℃ in a water bath, add 4.00mL of H2PdCl4 solution with a Pd concentration of 0.05g / mL and keep stirring at 70℃ for 5h, then add 1M sodium hydroxide solution to adjust the pH of the solution to 10, continue to keep stirring for 1h, finally stir at room temperature for 1h, filter, dry the catalyst in a vacuum oven at 110℃ for 24h, and finally grind into powder evenly to obtain 10wt.%Pd(OH)2 / NiTi-5 catalyst.
[0135] (4) 15 g HBIW, 127 ml DMF, 0.3 ml PhBr, 0.2 g of the above-prepared composite metal oxide-supported palladium catalyst, and 21 ml Ac2O were added to a 250 ml reactor in sequence, the air in the reactor was replaced with hydrogen, hydrogen was introduced, and the reaction was carried out for 24 hours under the reaction conditions of 0.5 MPa, 25° C., and a constant speed of 1000 r / min. The reaction was stopped, and the reaction solution was filtered using an organic filter membrane and washed with ethanol to obtain an off-white solid. The off-white solid is TADBIW and the catalyst. The yield of TADBIW was 75.94%. The solid was placed in a forced air drying oven at 110° C. and dried for 2 h, then taken out and weighed. The dried solid was poured into a reactor and 127 ml of acetic acid was added, and the temperature was set to 60° C. and stirred for 2 h. After 2 hours, stirring was stopped, 0.2 g 10 wt.% Pd(OH)2 / Ce catalyst and 18 ml deionized water were added, and H2 was passed to replace the air in the kettle. Then H2 was continued to be passed to make the pressure in the kettle at 1.5 MPa. The reaction temperature was set to 60°C and the reaction was started. The speed was kept constant at 1000 r / min. The reaction was stopped after 24 hours of reaction. The reaction solution was filtered using an organic filter membrane and washed with acetic acid. The obtained black solid was the catalyst. The solid was placed in a forced air drying oven at 110°C and dried for 2 hours, then taken out and weighed. After the TADBIW hydrogenolysis reaction was completed, HPLC was used to detect the purity of the product, and a TAIW yield of 56.68% was obtained.
[0136] Comparative Example 3 (Compared with Example 2)
[0137] Comparative Example 3 investigates the effect of feedstock concentration on the performance of selective catalytic hydrogenation reaction
[0138] (1) Preparation of TiO2
[0139] Pour 150ml of anhydrous ethanol into a beaker and place it on a magnetic stirrer to stir. Then, pour 10ml of tetrabutyl titanate into the anhydrous ethanol to prepare solution A. After stirring evenly, add 4ml of 22-28wt% ammonia water dropwise into solution A to prepare solution B. After a period of time, solution B turns white. Continue stirring for 24 hours and then centrifuge to obtain a white solid. Dry it in a forced air drying oven at 110°C for 2 hours, take it out, grind it, and obtain a titanium precursor.
[0140] (2) Preparation of different composite metal oxide supports MTi (M is another metal)
[0141] The carrier CeTi was prepared by an equal volume impregnation method: 2.00 g of the titanium precursor obtained in step (1) was weighed, 0.2523 g of Ce(NO3)3·6H2O was dissolved in an appropriate amount of water, and then poured into a culture dish containing the titanium precursor, and stirred continuously with a glass rod until the color was uniform, and then air-dried at room temperature. After air-drying, it was dried at 110°C in a forced air drying oven for 2 h, taken out and poured into a crucible, and heated to 450°C in a muffle furnace at 5°C / min, and calcined for 6 h to obtain Ce-TiO2 powder, which was recorded as CeTi-5;
[0142] (3) Preparation of Pd(OH)2 / MTi-x catalyst
[0143] Prepare Pd(OH)2 / MTi-x catalyst (10wt.%Pd) by deposition precipitation method: Take 1.8g of the carrier obtained in step (2) into a beaker, pour in 70ml of deionized water, stir and heat to 70℃ in a water bath, add 4.00mL of H2PdCl4 solution with a Pd concentration of 0.05g / mL, keep stirring at 70℃ for 5h, then add 1M sodium hydroxide solution to adjust the solution pH to 10, continue to keep stirring for 1h, finally stir at room temperature for 1h, filter, dry the catalyst in a vacuum oven at 110℃ for 24h, and finally grind into powder evenly to obtain 10wt.%Pd(OH)2 / CeTi-5 catalyst.
[0144] (4) 30 g HBIW, 100 ml DMF, 0.6 ml PhBr, 0.45 g of the prepared composite metal oxide supported palladium catalyst, and 30 ml Ac2O were added to a 250 ml reactor in sequence, the air in the reactor was replaced with hydrogen, hydrogen was introduced, and the reaction was carried out for 24 hours under the reaction conditions of 0.5 MPa, 25°C, and a constant speed of 1000 r / min. The reaction was stopped, and the reaction solution was filtered using an organic filter membrane and washed with ethanol to obtain an off-white solid. The off-white solid is TADBIW and the catalyst. The yield of TADBIW was 71.64%. The solid was placed in a forced air drying oven at 110°C and dried for 2 hours, then taken out and weighed. The dried solid was poured into a reactor and 127 ml of acetic acid was added, and the temperature was set to 60°C and stirred for 2 hours. After 2 hours, stirring was stopped, 0.6 g 10 wt.% Pd(OH)2 / CeTi-5 catalyst and 18 ml deionized water were added, and H2 was passed to replace the air in the kettle. Then H2 was continued to be passed to make the pressure in the kettle at 1.5 MPa. The reaction temperature was set to 60°C and the reaction was started. The speed was kept constant at 1000 r / min. The reaction was stopped after 24 hours of reaction. The reaction solution was filtered using an organic filter membrane and washed with acetic acid. The obtained black solid was the catalyst. The solid was placed in a forced air drying oven at 110°C and dried for 2 hours, then taken out and weighed. After the TADBIW hydrogenolysis reaction was completed, HPLC was used to detect the purity of the product, and a TAIW yield of 55.39% was obtained.
[0145] Comparative Example 4 (Compared with Example 2)
[0146] Comparative Example 4 investigates the effect of catalyst dosage on the performance of selective catalytic hydrogenation reaction
[0147] (1) Preparation of TiO2
[0148] Pour 150ml of anhydrous ethanol into a beaker and place it on a magnetic stirrer to stir. Then, pour 10ml of tetrabutyl titanate into the anhydrous ethanol to prepare solution A. After stirring evenly, add 4ml of 22-28wt% ammonia water dropwise into solution A to prepare solution B. After a period of time, solution B turns white. Continue stirring for 24 hours and then centrifuge to obtain a white solid. Dry it in a forced air drying oven at 110°C for 2 hours, take it out, grind it, and obtain a titanium precursor.
[0149] (2) Preparation of different composite metal oxide supports MTi (M is another metal)
[0150] The carrier CeTi was prepared by an equal volume impregnation method: 2.00 g of the titanium precursor obtained in step (1) was weighed, 0.2523 g of Ce(NO3)3·6H2O was dissolved in an appropriate amount of water, and then poured into a culture dish containing the titanium precursor, and stirred continuously with a glass rod until the color was uniform, and then air-dried at room temperature. After air-drying, it was dried at 110°C in a forced air drying oven for 2 h, taken out and poured into a crucible, and heated to 450°C in a muffle furnace at 5°C / min, and calcined for 6 h to obtain Ce-TiO2 powder, which was recorded as CeTi-5;
[0151] (3) Preparation of Pd(OH)2 / MTi-x catalyst
[0152] Prepare Pd(OH)2 / MTi-x catalyst (10wt.%Pd) by deposition precipitation method: take 1.8g of the carrier obtained in step (2) into a beaker, pour in 70ml of deionized water, stir and heat to 70℃ in a water bath, add 4.00mL of H2PdCl4 solution with a Pd concentration of 0.05g / mL and keep stirring at 70℃ for 5h, then add 1M sodium hydroxide solution to adjust the solution pH to 10, continue to keep stirring for 1h, finally stir at room temperature for 1h, filter, dry the catalyst in a vacuum oven at 110℃ for 24h, and finally grind into powder evenly to obtain 10wt.%Pd(OH)2 / CeTi-5 catalyst.
[0153] (4) 15 g HBIW, 127 ml DMF, 0.3 ml PhBr, 0.12 g of the above-prepared composite metal oxide-supported palladium catalyst, and 21 ml Ac2O were added to a 250 ml reactor in sequence, the air in the reactor was replaced with hydrogen, hydrogen was introduced, and the reaction was carried out for 24 hours under the reaction conditions of 0.5 MPa, 25°C, and a constant speed of 1000 r / min. The reaction was stopped, and the reaction solution was filtered using an organic filter membrane and washed with ethanol to obtain an off-white solid. The off-white solid is TADBIW and the catalyst. The yield of TADBIW is 68.55%. The solid was placed in a forced air drying oven at 110°C and dried for 2 hours, then taken out and weighed. The dried solid was poured into a reactor and 127 ml of acetic acid was added, and the temperature was set to 60°C and stirred for 2 hours. After 2 hours, stirring was stopped, 0.12g 10 wt.% Pd(OH)2 / CeTi-5 catalyst and 18ml deionized water were added, and H2 was passed to replace the air in the kettle. Then H2 was continued to be passed to make the pressure in the kettle at 1.5MPa. The reaction temperature was set to 60°C and the reaction was started. The speed was kept constant at 1000r / min. The reaction was stopped after 24 hours of reaction. The reaction solution was filtered using an organic filter membrane and washed with acetic acid. The obtained black solid was the catalyst. The solid was placed in a forced air drying oven at 110°C and dried for 2 hours, then taken out and weighed. After the TADBIW hydrogenolysis reaction was completed, HPLC was used to detect the purity of the product, and a TAIW yield of 45.36% was obtained.
[0154] Comparative Example 5 (Compared with Example 2)
[0155] Comparative Example 5 investigates the effect of hydrogen pressure on the performance of selective catalytic hydrogenation reaction
[0156] (1) Preparation of TiO2
[0157] Pour 150ml of anhydrous ethanol into a beaker and place it on a magnetic stirrer for stirring. Then, pour 10ml of tetrabutyl titanate into the anhydrous ethanol to obtain solution A. After stirring evenly, add 4ml of 22-28wt% ammonia water dropwise into solution A to obtain solution B. After a period of time, solution B turns white. Continue stirring for 24 hours and centrifuge to obtain a white solid. Dry it in a forced air drying oven at 110°C for 2 hours, take it out, grind it, and obtain a titanium precursor.
[0158] (2) Preparation of different composite metal oxide supports MTi (M is another metal)
[0159] The carrier CeTi was prepared by an equal volume impregnation method: 2.00 g of the titanium precursor obtained in step (1) was weighed, 0.2523 g of Ce(NO3)3·6H2O was dissolved in an appropriate amount of water, and then poured into a culture dish containing the titanium precursor, and stirred continuously with a glass rod until the color was uniform, and then air-dried at room temperature. After air-drying, it was dried at 110°C in a forced air drying oven for 2 h, taken out and poured into a crucible, and heated to 450°C in a muffle furnace at 5°C / min, and calcined for 6 h to obtain Ce-TiO2 powder, which was recorded as CeTi-5;
[0160] (3) Preparation of Pd(OH)2 / MTi-x catalyst
[0161] Prepare Pd(OH)2 / MTi-x catalyst (10wt.%Pd) by deposition precipitation method: take 1.8g of the carrier obtained in step (2) into a beaker, pour in 70ml of deionized water, stir and heat to 70℃ in a water bath, add 4.00mL of H2PdCl4 solution with a Pd concentration of 0.05g / mL and keep stirring at 70℃ for 5h, then add 1M sodium hydroxide solution to adjust the solution pH to 10, continue to keep stirring for 1h, finally stir at room temperature for 1h, filter, dry the catalyst in a vacuum oven at 110℃ for 24h, and finally grind into powder evenly to obtain 10wt.%Pd(OH)2 / CeTi-5 catalyst.
[0162] (4) 15 g HBIW, 127 ml DMF, 0.3 ml PhBr, 0.2 g of the prepared composite metal oxide supported palladium catalyst, and 21 ml Ac2O were added to a 250 ml reactor in sequence, the air in the reactor was replaced with hydrogen, hydrogen was introduced, and the reaction was carried out for 24 hours under the reaction conditions of 1.2 MPa, 25° C., and a constant speed of 1000 r / min. The reaction was stopped, and the reaction solution was filtered using an organic filter membrane and washed with ethanol to obtain an off-white solid. The off-white solid is TADBIW and the catalyst. The yield of TADBIW is 66.55%. The solid was placed in a forced air drying oven at 110° C. and dried for 2 h, then taken out and weighed. The dried solid was poured into a reactor and 127 ml of acetic acid was added, and the temperature was set to 60° C. and stirred for 2 h. After 2 hours, stirring was stopped, 0.2 g 10 wt.% Pd(OH)2 / CeTi-5 catalyst and 18 ml deionized water were added, and H2 was passed to replace the air in the kettle. Then H2 was continued to be passed to make the pressure in the kettle at 1.3 MPa. The reaction temperature was set to 60°C and the reaction was started. The speed was kept constant at 1000 r / min. The reaction was stopped after 24 hours of reaction. The reaction solution was filtered using an organic filter membrane and washed with acetic acid. The obtained black solid was the catalyst. The solid was placed in a forced air drying oven at 110°C and dried for 2 hours, then taken out and weighed. After the TADBIW hydrogenolysis reaction was completed, HPLC was used to detect the purity of the product, and a TAIW yield of 60.57% was obtained.
[0163] Comparative Example 6 (Compared with Example 2)
[0164] Comparative Example 6 investigates the effect of reaction temperature on the performance of selective catalytic hydrogenation
[0165] (1) Preparation of TiO2
[0166] Pour 150ml of anhydrous ethanol into a beaker and place it on a magnetic stirrer for stirring. Then, pour 10ml of tetrabutyl titanate into the anhydrous ethanol to obtain solution A. After stirring evenly, add 4ml of 22-28wt% ammonia water dropwise into solution A to obtain solution B. After a period of time, solution B turns white. Continue stirring for 24 hours and centrifuge to obtain a white solid. Dry it in a forced air drying oven at 110°C for 2 hours, take it out, grind it, and obtain a titanium precursor.
[0167] (2) Preparation of different composite metal oxide supports MTi (M is another metal)
[0168] The carrier CeTi was prepared by an equal volume impregnation method: 2.00 g of the titanium precursor obtained in step (1) was weighed, 0.2523 g of Ce(NO3)3·6H2O was dissolved in an appropriate amount of water, and then poured into a culture dish containing the titanium precursor, and stirred continuously with a glass rod until the color was uniform, and then air-dried at room temperature. After air-drying, it was dried at 110°C in a forced air drying oven for 2 h, taken out and poured into a crucible, and heated to 450°C in a muffle furnace at 5°C / min, and calcined for 6 h to obtain Ce-TiO2 powder, which was recorded as CeTi-5;
[0169] (3) Preparation of Pd(OH)2 / MTi-x catalyst
[0170] Prepare Pd(OH)2 / MTi-x catalyst (10wt.%Pd) by deposition precipitation method: take 1.8g of the carrier obtained in step (2) into a beaker, pour in 70ml of deionized water, stir and heat to 70℃ in a water bath, add 4.00mL of H2PdCl4 solution with a Pd concentration of 0.05g / mL and keep stirring at 70℃ for 5h, then add 1M sodium hydroxide solution to adjust the solution pH to 10, continue to keep stirring for 1h, finally stir at room temperature for 1h, filter, dry the catalyst in a vacuum oven at 110℃ for 24h, and finally grind into powder evenly to obtain 10wt.%Pd(OH)2 / CeTi-5 catalyst.
[0171] (4) 15 g HBIW, 127 ml DMF, 0.3 ml PhBr, 0.2 g of the above-prepared composite metal oxide-supported palladium catalyst, and 21 ml Ac2O were added to a 250 ml reactor in sequence, the air in the reactor was replaced with hydrogen, hydrogen was introduced, and the reaction was carried out for 24 hours under the reaction conditions of 0.5 MPa, 30°C, and a constant speed of 1000 r / min. The reaction was stopped, and the reaction solution was filtered using an organic filter membrane and washed with ethanol to obtain an off-white solid. The off-white solid is TADBIW and the catalyst. The yield of TADBIW is 45.52%. The solid was placed in a forced air drying oven at 110°C and dried for 2 hours, then taken out and weighed. The dried solid was poured into a reactor and 127 ml of acetic acid was added, and the temperature was set to 55°C and stirred for 2 hours. After 2 hours, stirring was stopped, 0.2 g 10 wt.% Pd(OH)2 / CeTi-5 catalyst and 18 ml deionized water were added, and H2 was passed to replace the air in the kettle. Then H2 was continued to be passed to make the pressure in the kettle at 1.5 MPa. The reaction temperature was set to 55°C and the reaction was started. The speed was kept constant at 1000 r / min. The reaction was stopped after 24 hours of reaction. The reaction solution was filtered using an organic filter membrane and washed with acetic acid. The obtained black solid was the catalyst. The solid was placed in a forced air drying oven at 110°C and dried for 2 hours, then taken out and weighed. After the TADBIW hydrogenolysis reaction was completed, HPLC was used to detect the purity of the product, and a TAIW yield of 49.44% was obtained.
[0172] Comparative Example 7 (Compared with Example 2)
[0173] Comparative Example 7 investigates the effect of the mass fraction of Pd loaded on the performance of selective catalytic hydrogenation reaction
[0174] (1) Preparation of TiO2
[0175] Pour 150ml of anhydrous ethanol into a beaker and place it on a magnetic stirrer to stir. Then, pour 10ml of tetrabutyl titanate into the anhydrous ethanol to prepare solution A. After stirring evenly, add 4ml of 22-28wt% ammonia water dropwise into solution A to prepare solution B. After a period of time, solution B turns white. Continue stirring for 24 hours and then centrifuge to obtain a white solid. Dry it in a forced air drying oven at 110°C for 2 hours, take it out, grind it, and obtain a titanium precursor.
[0176] (2) Preparation of different composite metal oxide supports MTi (M is another metal)
[0177] The carrier CeTi was prepared by an equal volume impregnation method: 2.00 g of the titanium precursor obtained in step (1) was weighed, 0.2523 g of Ce(NO3)3·6H2O was dissolved in an appropriate amount of water, and then poured into a culture dish containing the titanium precursor, and stirred continuously with a glass rod until the color was uniform, and then air-dried at room temperature. After air-drying, it was dried at 110°C in a forced air drying oven for 2 h, taken out and poured into a crucible, and heated to 450°C in a muffle furnace at 5°C / min, and calcined for 6 h to obtain Ce-TiO2 powder, which was recorded as CeTi-5;
[0178] (3) Preparation of Pd(OH)2 / MTi-x catalyst
[0179] Prepare Pd(OH)2 / MTi-x catalyst (3wt.%Pd) by deposition precipitation method: take 1.94g of the carrier obtained in step (2) into a beaker, pour in 70ml of deionized water, stir and heat to 70℃ in a water bath, add 1.20mL of H2PdCl4 solution with a Pd concentration of 0.05g / mL and keep stirring at 70℃ for 5h, then add 1M sodium hydroxide solution to adjust the solution pH to 10, continue to keep stirring for 1h, finally stir at room temperature for 1h, filter, dry the catalyst in a vacuum oven at 110℃ for 24h, and finally grind into powder evenly to obtain 3wt.%Pd(OH)2 / CeTi-5 catalyst.
[0180] (4) 15 g HBIW, 127 ml DMF, 0.3 ml PhBr, 0.2 g of the above-prepared composite metal oxide-supported palladium catalyst, and 21 ml Ac2O were added to a 250 ml reactor in sequence, the air in the reactor was replaced with hydrogen, hydrogen was introduced, and the reaction was carried out for 24 hours under the reaction conditions of 0.5 MPa, 25° C., and a constant speed of 1000 r / min. The reaction was stopped, and the reaction solution was filtered using an organic filter membrane and washed with ethanol to obtain an off-white solid. The off-white solid is TADBIW and the catalyst. The yield of TADBIW is 60.54%. The solid was placed in a forced air drying oven at 110° C. and dried for 2 h, then taken out and weighed. The dried solid was poured into a reactor and 127 ml of acetic acid was added, and the temperature was set to 60° C. and stirred for 2 h. After 2 hours, stirring was stopped, 0.2g 3wt.% Pd(OH)2 / CeTi-5 catalyst and 18ml deionized water were added, and H2 was passed to replace the air in the kettle. Then H2 was continued to be passed to make the pressure in the kettle at 1.5MPa. The reaction temperature was set to 60°C and the reaction was started. The speed was constant at 1000r / min. The reaction was stopped after 24 hours of reaction. The reaction solution was filtered using an organic filter membrane and washed with acetic acid. The obtained black solid was the catalyst. The solid was placed in a forced air drying oven at 110°C and dried for 2 hours, then taken out and weighed. After the TADBIW hydrogenolysis reaction was completed, HPLC was used to detect the purity of the product, and a TAIW yield of 44.53% was obtained.
Claims
1. A composite metal oxide supported palladium catalyst, characterized in that: The composite metal oxide supported palladium catalyst comprises a composite metal oxide carrier and an active component Pd(OH)2 supported on the carrier, wherein the loading amount of the active component = m Pd / (m Pd +m 载体 )×100%=5-10%, where m Pd It refers to the mass of palladium contained in the palladium precursor added during the preparation of the composite metal oxide-supported palladium catalyst; The composite metal oxide carrier is prepared by the following method: using titanate as a titanium source, obtaining titanium dioxide gel by a sol-gel method, and obtaining a titanium precursor after drying and grinding; loading a metal M precursor onto the titanium precursor by an impregnation method, and then drying and calcining to obtain a composite metal oxide carrier; the metal M precursor is selected from at least one of Zr(NO3)4·5H2O, SnCl2, Ce(NO3)3·6H2O, La(NO3)3·6H2O and Mn(NO3)2·4H2O; the titanium precursor and the metal M precursor are mixed according to the metal M loading amount x%=m 金属M氧化物 / m TiO2 ×100% = 1-9% feed, where m 金属M氧化物 It is the total mass of metal M oxide converted from the mass of metal M element contained in the metal M precursor, m TiO2 Refers to the mass of the titanium precursor.
2. The composite metal oxide supported palladium catalyst as claimed in claim 1, characterized in that: The titanate is at least one of tetraethyl titanate, tetraisopropyl titanate and tetrabutyl titanate.
3. The composite metal oxide supported palladium catalyst as claimed in claim 1, characterized in that: The calcination conditions are: heating to 450-500°C at 5-10°C / min in a muffle furnace and calcining for 6-8h.
4. The composite metal oxide supported palladium catalyst as claimed in claim 1, characterized in that: x is 3-9, preferably 3-5.
5. The composite metal oxide supported palladium catalyst as claimed in claim 1, characterized in that: The loading of active ingredient was 10%.
6. A method for preparing a composite metal oxide-supported palladium catalyst as claimed in any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: (1) obtaining a composite metal oxide support; (2) The composite metal oxide supported palladium catalyst was prepared by the deposition precipitation method.
7. The preparation method according to claim 6, characterized in that: Step (2) is specifically implemented as follows: disperse the composite metal oxide carrier in deionized water, stir and heat to 50-80° C. in a water bath, add the palladium precursor solution and stir at 50-80° C. for 4-6 hours, then adjust the solution pH to 9-11, continue to stir at this temperature for 1-2 hours, finally stir at room temperature for 1-2 hours, filter with suction, dry, and finally grind into powder uniformly to obtain a composite metal oxide-supported palladium catalyst.
8. The preparation method according to claim 7, characterized in that: In step (2), the palladium precursor is at least one of palladium chlorate, palladium nitrate, and dichlorotetraamminepalladium.
9. Use of the composite metal oxide supported palladium catalyst as claimed in any one of claims 1 to 5 in the synthesis of TAIW via two-step hydrogenolysis of HBIW.
10. The use according to claim 9, characterized in that: The synthesis of TAIW by two-step hydrogenolysis of HBIW is specifically carried out according to the following steps: Step 1: HBIW, DMF, PhBr, composite metal oxide-supported palladium catalyst, and Ac2O are added to a reactor in sequence, the air in the reactor is replaced with hydrogen, hydrogen is introduced, and the reaction is carried out for 18-36 hours under the reaction conditions of 0.5-1MPa, 25-40°C, and a constant speed of 500-1000r / min, the reaction is stopped, and an off-white solid is obtained by filtering and washing. The off-white solid is TADBIW and the catalyst, and the solid is placed in a blast drying oven at 90-120°C and dried for 2-4 hours; Step 2: Pour the solid obtained in step 1 into a reactor and add an appropriate amount of acetic acid, set the temperature to 60-70°C and stir for 1-4h, then stop stirring, add a certain amount of composite metal oxide-loaded palladium catalyst and an appropriate amount of deionized water, then pass H2 to replace the air in the reactor, and then continue to pass H2 to make the pressure in the reactor at 1.5-3MPa, set the reaction temperature to 60-70°C and start the reaction, keep the rotation speed constant at 500-1000r / min, stop the reaction after 12-24h, filter and wash, the obtained black solid is the catalyst, and the obtained filtrate is the solution containing TAIW.
Citation Information
Patent Citations
Application of palladium-based bimetallic catalyst in catalytic hydrogenolysis reaction of HBIW
CN106946894A
Preparation method of palladium hydroxide carbon catalyst for removing N-benzyl
CN113680362A
Preparation and application of hydrogenolysis catalyst
CN115591544A
Method for preparing hydrogenation catalyst by hydrothermal method and application of catalyst
CN116116404A
Method for producing tetraacetyl hexaazaisowurtzitane
CN116535414A